Proton gradients across the coral calcifying cell layer: Effects of light, ocean acidification and carbonate chemistry - Venn, Alexander A.; Tambutté, Eric; Comeau, Steeve; Tambutté, Sylvie (Frontiers in Marine Science, 2022)
In corals, pH regulation of the extracellular calcifying medium (ECM) by the calcifying cell layer is a crucial step in the calcification process and is potentially important to influencing how corals respond to ocean acidification. Here, we analyzed the growing edge of the reef coral Stylophora pistillata to make the first characterization of the proton gradient across the coral calcifying epithelium. At seawater pH 8 we found that while the calcifying epithelium elevates pH in the ECM on its apical side above that of seawater, pH on its basal side in the mesoglea is markedly lower, highlighting that the calcifying cells are exposed to a microenvironment distinct from the external environment. Coral symbiont photosynthesis elevates pH in the mesoglea, but experimental ocean acidification and decreased seawater inorganic carbon concentration lead to large declines in mesoglea pH relative to the ECM, which is maintained relatively stable. Together, our results indicate that the coral calcifying epithelium is functionally polarized and that environmental variation impacts pHECM regulation through its effects on the basal side of the calcifying cells.